MANTRA TUKANG PIJIT: SEBUAH ANALISIS SEMIOLOGI BARTHES - Misbah Priagung Nursalim; Rima Tiana (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2018)
Abstract: A charm is a subgenre of old poetry that is still considered to have strength. Because the power possessed by a charm makes people consider it sacred. However, apart from that, the mantra is only a part of literary work which contains meaning and of course there is no magical element. This study discusses the meaning in massage charm in Pondok Petir area. The author uses Roland Barthes's semiology theory to analyze the meaning of the charm. This study also uses descriptive qualitative methods to analyze the meaning and form of charms. The results prove that the massage charm does not have magical power. The charm is only an old literary work in which it contains the meaning of certain commands depending on the material function. Because charms are old poems, so charms also pay attention to the beauty of the shape and the sound.Abstrak: Mantra merupakan subgenre puisi lama yang sampai saat ini masih dianggap memiliki kekuatan sehingga membuat masyarakat menganggapnya suci. Namun, terlepas dari itu, mantra hanyalah sebuah bagian dari karya sastra yang di dalamnya menyimpan makna dan tentu tidak ada unsur magis. Penelitian ini secara umum membahas mengenai studi makna pada mantra tukang pijit di daerah Pondok Petir. Penulis menggunakan teori semiologi Roland Barthes untuk mengkaji makna yang terkandung di dalam mantra tersebut. Metode kualitiatif deskriptif digunakan untuk menganalisis makna dan bentuk mantra. Hasil penelitian ini membuktikan bahwa mantra tukang pijit tidak mempunyai kekuatan magis. Mantra hanya karya sastra lama yang di dalamnya menyimpan makna berupa perintah tertentu tergantung fungsi matera tersebut. Karena mantra merupakan puisi lama, jadi mantera juga memperhatikan keindahan bentuk dan bunyi bahasanya.